Comfortably Numb? Revisiting and Re-Specifying the Relationship Between Health Strain and Substance Use - Lowe, C. Cory (Crime & delinquency, 2020)
Studies have found a positive linear relationship between health strain and substance use; however, they often omit potential confounders such as self-control, social bonds, and peer use. Furthermore, there are several reasons to believe the relationship is curvilinear according to Agnew’s general strain theory. Using data from the National Longitudinal Study of Adolescent to Adult Health, we examine whether the linear relationship persists after including confounders and we test the hypothesized curvilinear relationship. Results provide little support for the linear relationship; however, the hypothesized curvilinear relationship is supported in multiple alcohol and marijuana use models. In addition, there is little evidence that health strain is mediated by depressive symptoms. Policy implications, limitations, and directions for research are discussed.